Airborne particulate matter pollution in urban China: a chemical mixture perspective from sources to impacts. Issue 4 (13th November 2016) - Jin, Ling; Luo, Xiaosan; Fu, Pingqing; Li, Xiangdong
Abstract: Rapid urban and industrial development has resulted in severe air-pollution problems in developing countries such as China, especially in highly industrialized and populous urban clusters. Dissecting the complex mixtures of airborne particulate matter (PM) has been a key scientific focus in the last two decades, leading to significant advances in understanding physicochemical compositions for comprehensive source apportionment. However, identifying causative components with an attributable link to population-based health outcomes remains a huge challenge. The microbiome, an integral dimension of the PM mixture, is an unexplored frontier in terms of identities and functions in atmospheric processes and human health. In this review, we identify the major gaps in addressing these issues, and recommend a holistic framework for evaluating the sources, processes and impacts of atmospheric PM pollution. Such an approach and the knowledge generated will facilitate the formulation of regulatory measures to control PM pollution in China and elsewhere.